Feasibility Testing of an “IOT-based Multi-modal Personalized m-Health System(IMPMS) Used for Loneliness Detection” in Finnish immigrants - Farzanehkari, Parisa (My University, 2023)
Background: Loneliness is a global issue with physical and psychological consequences. Immigration can increase the risk of loneliness. The Domino project aims to identify loneliness using advanced technologies and automated data collection. Purpose: This study tested the feasibility of IoT-based Multi-modal Personalized M-health System (IMPMS) in detecting loneliness among Finnish immigrants. Feasibility was evaluated through participant adherence and engagement, technical issue identification and resolution, and exploring the link between loneliness and sleep quality. Methods: A longitudinal study was conducted with 20 lonely immigrants over a four-week period. Participants wore the Oura ring and Samsung watch, used applications on their phones, and completed surveys. Adherence was measured by tracking wearable usage and Ecological momentary assessment (EMA) survey response rates. Engagement was assessed using the TWEETs survey. Technical issues were identified and resolved during the study. The association between loneliness and sleep quality was analyzed using Pearson correlation testing. Results: Participants did not wear the Oura ring for an average of 2.5 hours/day and the Samsung watch for 14.5 hours/day. The average response rate to surveys was 40%. Participant engagement remained consistent throughout the study. Technical issues related to sensor quantity and quality were resolved. The IMPMS did not find a statistically significant correlation between loneliness and sleep quality. Conclusions: This study gave insights about the feasibility of using IMPMS to detect loneliness in Finnish immigrants over a four-week period. Based on the findings, it is recommended to make modifications such as reducing the frequency of EMA questions and addressing the system issues identified in this study to enhance the system’s feasibility. Keywords: Feasibility, “Self-monitoring system”, “wearable devices”, “internet of things”, “feasibility”, health, Immigrant, and loneliness. feasibility.
Keywords: Feasibility, “Self-monitoring system”, “wearable devices”, “internet of things”, “feasibility”, health, Immigrant, loneliness